Effectiveness of the Village Financial Information System in Supporting Village Financial Governance in Werot Village, North Minahasa Regency, Indonesia - Kaunang, Susana; Biringan, Julien; Tarore, Steven V. (International Journal of Information Technology and Education, 2026)
The study addresses the growing demand for transparent, accountable, orderly, and digitally supported village financial governance. Using a qualitative descriptive design, the article collected data through interviews, observation, and documentation involving village officials, financial operators, planning actors, village assistants, and subdistrict officials. The findings indicate that Siskeudes has supported a more structured and standardized financial administration process, but it has not yet operated with full effectiveness. Delayed data entry, errors in administration, repeated report corrections, late submission, limited public transparency, and dependence on a few technical users continue to constrain the system. The main inhibiting factors include uneven human resource capacity, inadequate technological infrastructure, weak administrative discipline, limited internal coordination, insufficient contextual guidance and supervision, and difficulty adapting to regulatory changes. The article argues that Siskeudes should be understood as a socio-technical governance system rather than merely a software application. Its effectiveness depends on the alignment of people, procedures, technology, data, leadership, and accountability culture. The article proposes an integrated strengthening strategy consisting of continuous capacity building, infrastructure improvement, workflow discipline, collective coordination, contextual supervision, and citizen-friendly transparency. The study contributes to public administration literature by demonstrating that digital village financial governance requires not only regulatory compliance but also organizational learning and institutional readiness.